If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19x + 11y = 20900 Solving 19x + 11y = 20900 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11y' to each side of the equation. 19x + 11y + -11y = 20900 + -11y Combine like terms: 11y + -11y = 0 19x + 0 = 20900 + -11y 19x = 20900 + -11y Divide each side by '19'. x = 1100 + -0.5789473684y Simplifying x = 1100 + -0.5789473684y
| 20=2(6)-8 | | -6(5k+4)=-114 | | 8.92x/133.8=(7.17)(35.85) | | 2x-8=2x-8 | | 36=3y-15 | | 6x^5/4x | | 2.5x^2=3x | | -16-3x=5-6x | | .11x+.05(7500-x)=675 | | 2+3(6)= | | 5ln(5x+2)=22 | | 2=m^2-7 | | 5×5/6 | | Y=0.002x+0.000 | | -4x+3=-5x-4 | | 3(11x-7)=13+25 | | 3x/2-x/3=5(x-4)/6 | | 64x+44=-20 | | 64x+4=-20 | | (x-10)/75=8 | | -1/2(1-5p)=2/3(p-7)-5 | | 0=x^2-6.6x+8 | | 96+x=7x+36 | | 5ax+7a-10x-14= | | 7x/8-(x-2)=12 | | p-(-13)ifp=-6 | | 1.67+x^3=1 | | p-(-13)p=-6 | | b(8a+7c)-2d(8a+7c)= | | 13x-12y+14z=12y+14z+48x | | (3h-4)(2h+3)=(3h-2)(2h+1) | | 5log(3x-2)=3 |